(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
Framework Decision 2008/909/JHA on the application of the principle of mutual recognition for judgments imposing custodial sentences or measures involving deprivation of liberty is an EU instrument intended to facilitate the transfer of prisoners between the EU members, allowing at the same time the possibility of the transfer without the prisoner`s consent. Even though the purpose of this instrument, as stated in recital 9, is to facilitate the social rehabilitation, its application can raise questions regarding the fulfilment of this goal and regarding the protection of the fundamental rights in the transfer proceedings. That has been recognised on the EU level, hence research and analysis of the implementation of FD 909 have recently been conducted, especially concerning the detention conditions across the EU and limits to the mutual trust presumption in the light of the CJEU judgement Aranyosi/ Căldăraru. The paper analyses some key issues regarding the application of the principle of mutual recognition in this area: possibilities of social rehabilitation of the sentenced person, procedural rights in the transfer proceedings, possible violations of the prohibition of torture, inhuman and degrading treatment due to inadequate detention conditions in the executing member state. The paper also analyses the connection between this Framework decision and the Framework decision on the European arrest warrant. The special attention is given to the relevant jurisprudence of the Court of Justice of the EU. Along with the EU framework, the paper provides an overview of the Croatian legislation and jurisprudence regarding the mentioned subject.